Sistem pengelolaan limbah pada inna grand bali beach hotel di sanur - Said, Asia; Putra, Agus Muriawan; Sutaguna, I Nyoman Tri (Jurnal Kepariwisataan dan Hospitalitas, 2024)
Inna Grand Bali Beach Hotel is one of the five-star and international standard hotels in Bali located on the Sanur beach. This study aims to determine the waste management system contained in the Inna Grand Bali Beach Hotel in Sanur. Data collection is done by observation, interviews, documentation, and literature study. The technique of determining the informants in this study used purposive sampling. And for the data analysis technique is done with descriptive qualitative that is using in-depth interview. The results showed that the waste management and utilization system at Inna Grand Bali Beach were very good. Because according to the results of interviews of researchers with the community around the hotel, they said that there was no impact of hotel waste on the community and the surrounding environment. And even from the hotel until now have not received any complaints from the public. Therefore, waste management and environmental conservation efforts by the hotel are very effective in preventing environmental polluters. Hotel Grand Inna applies EM4 technology in its waste management and cooperates with third parties, namely the community in the utilization of their waste. Meanwhile, for liquid waste, the management uses a Wastewater Treatment Plant (IPAL). Which with the help of EM4 technology can help in the management of liquid waste because it can reduce the fat that collects in the grease trap so that it dissolves with wastewater. The clean wastewater can be used for crops and golf courses. Meanwhile, the utilization of the waste is through recycling and composting. This is done to reduce the volume of waste, the compost can be used to fertilize hotel gardens and parks. Keywords: Waste Management, Grand Inna Hotel, Sanur.